Recent progress in carbon dots for anti-pathogen applications in oral cavity - Jiang, Yuying; Yin, Chuqiang; Mo, Jianning; Wang, Xiaoyu; Wang, Ting; Li, Guotai; Zhou, Qihui (Frontiers in Cellular and Infection Microbiology, 2023)
Background Oral microbial infections are one of the most common diseases. Their progress not only results in the irreversible destruction of teeth and other oral tissues but also closely links to oral cancers and systemic diseases. However, traditional treatment against oral infections by antibiotics is not effective enough due to microbial resistance and drug blocking by oral biofilms, along with the passive dilution of the drug on the infection site in the oral environment. Aim of review Besides the traditional antibiotic treatment, carbon dots (CDs) recently became an emerging antimicrobial and microbial imaging agent because of their excellent (bio)physicochemical performance. Their application in treating oral infections has received widespread attention, as witnessed by increasing publication in this field. However, to date, there is no comprehensive review available yet to analyze their effectiveness and mechanism. Herein, as a step toward addressing the present gap, this review aims to discuss the recent advances in CDs against diverse oral pathogens and thus propose novel strategies in the treatment of oral microbial infections. Key scientific concepts of review In this manuscript, the recent progress of CDs against oral pathogens is summarized for the first time. We highlighted the antimicrobial abilities of CDs in terms of oral planktonic bacteria, intracellular bacteria, oral pathogenic biofilms, and fungi. Next, we introduced their microbial imaging and detection capabilities and proposed the prospects of CDs in early diagnosis of oral infection and pathogen microbiological examination. Lastly, we discussed the perspectives on clinical transformation and the current limitations of CDs in the treatment of oral microbial infections.